2019
DOI: 10.1109/mcg.2019.2901428
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Analytics Lessons From the Electronic Visualization Laboratory: A 25-Year Perspective

Abstract: This article provides a 25 year-long perspective on Immersive Analytics through the lens of firstin-kind technological advancements introduced at the Electronic Visualization Laboratory, University of Illinois at Chicago, along with the challenges and lessons learned from multiple Immersive Analytics projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In support of local collaboration, CAVE developers have noted that their design has shifted from being a system within the room to being the entire room. Their goal is a war room [88] to support co-located collaboration [128], but they must fall back on other formats (such as video conferencing) to support distance collaborators. In this scenario, participants are capable of hosting a traditional meeting and taking advantage of immersive features on demand.…”
Section: C13: Integrating Current Collaboration Practicementioning
confidence: 99%
“…In support of local collaboration, CAVE developers have noted that their design has shifted from being a system within the room to being the entire room. Their goal is a war room [88] to support co-located collaboration [128], but they must fall back on other formats (such as video conferencing) to support distance collaborators. In this scenario, participants are capable of hosting a traditional meeting and taking advantage of immersive features on demand.…”
Section: C13: Integrating Current Collaboration Practicementioning
confidence: 99%
“…The authors have found that device-based interactions are ideal for larger, room-based collaborative installations because they provide precise navigation and high fidelity data streams even in groups of people, and they are less susceptible to some of the current technological hurdles of 3D sensors like limited tracking areas, occlusion and consistent user identification (though the technology is rapidly evolving and the new Microsoft Kinect Azure seems to have potentially solved several of these issues). Work at the EVL, "further points to the benefits of embodied navigation in the context of large spatial datasets" (Marai [11]). The ultrasonic wand (via a grid of ultrasonic emitters in the ceiling, and an array of microphones in the wand) provides a continuous stream of data at 60-70 frames per second that includes the wand position, orientation, and button states.…”
Section: Gesture and Visualizationmentioning
confidence: 99%
“…Another way to immerse the user into data is to utilize a wall-sized high-resolution display. Due to inherent characteristics—namely large display real estate and the vast amount of pixels - large, high-resolution displays can cover the entire field of view of the user and provide the ability to scrutinize details within context (Marai et al, 2019 ). Thus, such displays are highly suitable for immersive analytics.…”
Section: Introductionmentioning
confidence: 99%
“…Marai et al mentioned the following advantages of large, high-resolution displays in the sensemaking context: large display size and pixel density to show multiple representations simultaneously; ability to show context plus detail; enough space for group work (Marai et al, 2019 ). Systems using large, high-resolution displays often implement a whiteboard or tabletop metaphor with novel interaction techniques and devices to resemble well-known collaboration principles used in real-life communication (Guimbretière et al, 2001 ; Scott et al, 2003 , 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation